Inequality of opportunities among ethnic groups in the Philippines - Celia M. Reyes; Christian D. Mina; Ronina D. Asis (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
This paper contributes to the scant body of literature on inequalities among and within ethnic groups in the Philippines by examining both the vertical and horizontal measures in terms of opportunities in accessing basic services such as education, electricity, safe water, and sanitation. The study also provides a glimpse of the patterns of inequality in Mindanao. The results show that there are significant inequalities in opportunities in accessing basic services within and among ethnic groups in the Philippines. Muslims (particularly indigenous people) are the worst-off ethnic groups while the non-indigenous/non-Muslim groups are the better-off groups. Disparities in terms of literacy rate and access to electricity and sanitation between ethnic groups, however, appear to be narrowing between 2000 and 2010.
Keywords: J15; I24; Z13; C13; 330; ethnic group; horizontal inequality; indigenous people; inequality of opportunities; Mindanao; Philippines